UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT BELAJAR DI MI LUQMANUL HAKIM BATUMARTA TAHUN PELAJARAN 2022/2023 - Aminarsih; Eko Suncaka; Mujiyatun (UNISAN JURNAL, 2023)
This study aims to analyze the factors influencing students’ learning interest at MI Luqmanul Hakim Batumarta and the strategies used by Islamic religious education teachers to enhance students’ learning interest. The method used in this study is qualitative research with data collection techniques such as observation, interviews, and documentation. The results of this study indicate that factors such as lack of learning interest among students, unfavorable learning environment, lack of interesting learning media, and lack of family support can be barriers to enhancing students’ learning interest. However, effective strategies, such as providing motivation and interesting learning methods, creating a conducive learning environment, and involving families in the education process, can help Islamic religious education teachers to enhance students’ learning interest. Teachers face challenges such as lack of time, lack of funds, and lack of school support. The solutions that can be provided include teacher training and skill development, collaboration between schools, teachers, parents, and the community, and adequate allocation of funds for educational purposes. By implementing these solutions, it is hoped that students’ learning interest at MI Luqmanul Hakim Batumarta can be enhanced, and the quality of education at the school can be improved.